Closer - Gordon, Roderick; Williams, Brian James, 1958- (Somerset : Chicken House, 2010)
Will Burrows believes he is safe at the very center of the earth, in a world that no one knows exists, but the Styx are close behind and will follow him anywhere, while on the surface, Drake and some unlikely allies unearth some critical secrets.
5.9
5-8.
5-8
Keywords: Archaeology -- Juvenile fiction; Underground areas -- Juvenile fiction; Adventure and adventurers -- Fiction; Archaeology -- Fiction; Science fiction; Underground areas -- Fiction; Adventure fiction; Archeology -- Fiction; Science fiction; Underground areas -- Fiction; England -- Juvenile fiction; London (England) -- Juvenile fiction; England -- Fiction; London (England) -- Fiction; England -- Fiction; London (England) -- Fiction; Adventure fiction; Science fiction